2015
DOI: 10.4236/jwarp.2015.716113
|View full text |Cite
|
Sign up to set email alerts
|

pH Control during the Struvite Precipitation Process of Wastewaters

Abstract: The high concentration of phosphorus and nitrogen in wastewater and sludge could be lowered to a certain level by struvite (MgNH4PO4•6H2O) crystallization. One of the main factors for struvite formation is the solution pH. It can be adjusted by non-reagent carbon (CO2) dioxide stripping through the process of aeration. The intensity of the mass transfer between the air and the supernatant of dewatering sludge obtained from wastewater treatment plant is characterized by the volumetric liquid-side mass transfer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 30 publications
0
1
0
Order By: Relevance
“…This did not induce hydrolysis and/or co-precipitation of metallic ions. Some reports also showed that the CO 2 /SO 2 gases were bubbled into neutral or weakly alkaline leachates (Radev et al, 2015) but inappropriately into acidic leachate (Figure 2A). In addition, the pH decrease can be performed in two special ways.…”
Section: Ph Adjustment Toward Acidic Conditionsmentioning
confidence: 99%
“…This did not induce hydrolysis and/or co-precipitation of metallic ions. Some reports also showed that the CO 2 /SO 2 gases were bubbled into neutral or weakly alkaline leachates (Radev et al, 2015) but inappropriately into acidic leachate (Figure 2A). In addition, the pH decrease can be performed in two special ways.…”
Section: Ph Adjustment Toward Acidic Conditionsmentioning
confidence: 99%
“…Besides the direct reagent alkalization there, pH can be elevated by carbon dioxide (CO 2 ) stripping through aeration of the reagent mixture. Figure 3 shows the principal scheme of the striping system [28]. The mechanism of this treatment is based on the manipulation of the dissolved carbon dioxide mass balance in the liquid.…”
Section: Phosphorus In Soils and Plantsmentioning
confidence: 99%
“…The described mechanism seems to be appropriate in the case of sludge water treatment as it contains high amounts of organic matter which potentially enriches the liquid with CO 2 due to the microbial activity occurring in the suspension. It was found that the rate of pH elevation depends strongly on the spangling area of the air distribution system while the air flow rate does not influence considerably the dissolved oxygen level which governs the CO 2 stripping process [28]. The theoretically calculated values of the volumetric mass transfer coefficient have been compared with those obtained experimentally.…”
Section: Phosphorus In Soils and Plantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Perforated air stones with many holes are installed at the bottom of the reactor as aeration air holes. Increasing the pH using aeration will be faster using a lot of aerated air holes compared to fewer aerated air holes (Radev et al, 2015). The reactor struvite precipitation apparatus is shown in Figure 1.…”
Section: Reactor Preparationmentioning
confidence: 99%